Between ‘Freedom as Autonomy’ and ‘Freedom as Potentiality’: Artistic Work in a Participatory Culture - Vilstrup Holm, Ditte (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Contemporary cultural policy promotes the value of participatory practices, including participatory art. However, this emphasis renders cultural policy subject to the art community’s widespread and generalized suspicion that government initiatives instrumentalize artistic practices to serve purposes other than those pursued by artists themselves. This article addresses the relationship between participatory art, participatory culture and cultural policy, focusing in particular on notions of artistic autonomy. Specifically, the article uses organization theory’s discussion of freedom in work to frame art theory’s sustained, albeit differently conceptualized, preoccupation with notions of artistic autonomy in respect to the bureaucratic organization of life in modernity. Empirically, the article analyses an inspirational catalogue that promotes the use of participatory art and citizen involvement in public art projects as a way of challenging the art community’s generalized suspicion, while also suggesting that Danish arts policy is renegotiating the role of art in contemporary society by taking advantage of contemporary opportunities for seizing artistic freedom. Contemporary participatory culture, it is argued, conditions as well as promotes artistic practice, thus generating new artistic possibilities, although only to the extent that artists engage in collaboration with other organizations, including those affecting cultural policy.